2015
DOI: 10.1038/ncb3193
|View full text |Cite|
|
Sign up to set email alerts
|

The oncogene c-Jun impedes somatic cell reprogramming

Abstract: Oncogenic transcription factors are known to mediate the conversion of somatic cells to tumour or induced pluripotent stem cells (iPSCs). Here we report c-Jun as a barrier for iPSC formation. c-Jun is expressed by and required for the proliferation of mouse embryonic fibroblasts (MEFs), but not mouse embryonic stem cells (mESCs). Consistently, c-Jun is induced during mESC differentiation, drives mESCs towards the endoderm lineage and completely blocks the generation of iPSCs from MEFs. Mechanistically, c-Jun a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 68 publications
9
129
1
4
Order By: Relevance
“…Liu et al reported that c-JUN induces the EMT process and directly activates a group of genes including TWIST2, TGM2, DUSP5 and ETS1 [39]. In agreement with this report, these four genes are down-regulated after ectopic SPANXA expression.…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al reported that c-JUN induces the EMT process and directly activates a group of genes including TWIST2, TGM2, DUSP5 and ETS1 [39]. In agreement with this report, these four genes are down-regulated after ectopic SPANXA expression.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in apparent disagreement with the recent study by Liu et al ., that suggested an inhibitory role for c-JUN in reprogramming [21]. There are several differences between our study and the study by Liu et al , including the choice of cells and reprogramming conditions.…”
Section: Discussionmentioning
confidence: 56%
“…These data suggested that Fra1 loss from MEs is critical for their silencing and iPSC production. Overexpression of cJun, the binding partner of Fra1, was also detrimental for reprogramming (Fig 5H, S6M) (Liu et al, 2015) and produced similar expression changes as Fra1 overexpression (Fig 5J/K), suggesting that cJun may block reprogramming in synergy with Fra1.…”
Section: Resultsmentioning
confidence: 91%